Nanoemulsion Mouthwash Formulation of Bajakah Tampala (Spatholobus littoralis Hassk.) Skin Extract Against Candida albicans - Hamzah, Hasyrul; Gunawan, Dede Reza; Pratiwi, Sylvia Utami Tunjung; Bakhtiar, Muh. Irham; Pratama, Virgiawan Yoga; Subhan, Muhammad; Maulana, Riza (Borneo Journal of Pharmacy, 2024)
Candida albicans can cause two infections in humans: superficial and systemic. The ability of C. albicans to infect the host is influenced by virulence factors and character changes so that it can fool the immune system. From the character change factor, C. albicans can form a biofilm. This study aims to determine the good concentration in inhibiting and determine the antifungal and antibiofilm activity of nanoemulsion mouthwash formulation of bajakah tampala (Spatholobus littoralis Hassk) skin extract against C. albicans. This research was conducted with an experimental method. The formulation used a spontaneous magnetic stirrer technique to make nanoemulsion preparations. Antifungal and antibiofilm tests were carried out by dilution method using a 96-well plate and a microplate reader with a wavelength of 620 nm to determine the percentage inhibition against C. albicans and determine MIC50 and MBIC50. The results showed that the nanoemulsion mouthwash formulation of S. littoralis inhibited the planktonic and biofilm of C. albicans. The concentration of 1% is expressed as MIC50 and MBIC50. Therefore, the nanoemulsion formulation of S. littoralis extract could inhibit the growth of C. albicans in the oral cavity.